Citizenship and Social Exclusion at the Margins of the Welfare State - Takle, Marianne; Vedeler, Janikke Solstad; Schoyen, Mi Ah; Bøhler, Kjetil Klette; Falch-Eriksen, Asgeir (Social Welfare Around the World, 2023)
This book presents a critical account of how citizenship unfolds among socially marginalised groups in democratic welfare states. Legal, political and sociological perspectives are applied to offer an assessment of the extent and depth of citizenship for marginalised groups in countries which are expected to offer their members a highly inclusive form of citizenship. The book studies the legal and political status of members of a nation-state, and analyses how this is followed up in practice, by examining the subjective feelings of membership, belonging or identity, as well as opportunities to participate actively and be included in different areas of society. Showing how the welfare state and society treat citizens at risk of social exclusion and offering new insights into the conceptual interconnection between citizenship, social exclusion, and the democratic welfare state, the book will be of interest to all scholars, students and academics of social policy, social work and public policy.